PENGARUH METODE PERMAINAN KARTU TERHADAP PENINGAKATAN NILAI BELAJAR PSERTA DIDIK DI MTS HASYIM ASYA’ARI PAKIS KEMBAR KABUPATEN MALANG - Astika Sriyani; Ika Ratih Sulistiani; Muhammad Sulistiono (VICRATINA, 2019)
Thiss studyc aimsb tov describeb Islamicd educationq activitiesq carriedq outq atq Learning on Pai subjects uses the index card match treatment which will impose a 2-class system of control and experiment classes held at Mts Hasyim Asya'ari. This study uses several tests to determine the score obtained from the results of the application of the index card match method, namely the test instrument. the results of the Control group of 30 samples achieved by students amounted to 89. While the Experimental group of 30 samples achieved scores of students amounted to 99. And students in PAI class VII class Mts Hasyim Asya'ari showed that most student learning outcomes were in interval 89 -100. Keywords: card games, learning value